Saline infusion sonography effectiveness study - De Silva, A.W.S.S (My University, 2010)
Abnormal uterine bleeding is a common problem which makes women seek medical treatment. Although most of these women do not have any structural lesions some of them do have. Even though hysteroscopy and guided biopsy is the accepted gold standard to diagnose these lesions, majority of the Sri Lankan women are unable to enjoy it due to the lack of facilities. Saline infusion sonography is thought to be a successful alternative in the detection of structural lesions. This study was done to compare it's effectiveness with that of hysteroscopy and histology. To decide on the sensitivity, specificity, positive and negative predictive values and positive and .negative likelihood ratios of saline infusion sonography. Premenopausal women over the age of 40 years, presenting with abnormal uterine bleeding were selected for the study . They underwent saline infusion sonography, hysteroscopy and endometrial biopsy. Above parameters were calculated for saline infusion sonography taking hysteroscopy and histology as the gold standard. When analyzed including endometrial hyperplasia as pathology in calculations the sensitivity of SIS was 58.1 percent ; the specificity was 97.9 percent ; positive predictive value was 92.6percent and the negative predictive value was83.9percent . When the calculation. was done excluding hyperplasia the sensitivity 85.2 percent ; the specificity was 100 percent ; positive predictive value was 96.6 percent. Saline infusion sonography is as effective as hysteroscopy in detecting structural endometrial lesions